Development and verification of prognostic nomogram for ampullary carcinoma based on the SEER database - Tang, Nan; Chen, Zeng-Yin; Yang, Zhen; Shang, He-Zhen; Shi, Guang-Jun (Frontiers in Oncology, 2023)
Background: Ampullary carcinoma (AC) is a rare cancer of the digestive system that occurs in the ampulla at the junction of the bile duct and pancreatic duct. However, there is a lack of predictive models for overall survival (OS) and disease -specific survival (DSS) in AC. This study aimed to develop a prognostic nomogram for patients with AC using data from the Surveillance, Epidemiology, and End Results Program (SEER) database. Methods: Data from 891 patients between 2004 and 2019 were downloaded and extracted from the SEER database. They were randomly divided into the development group (70%) and the verification group (30%), and then univariate and multivariate Cox proportional hazards regression, respectively, was used to explore the possible risk factors of AC. The factors significantly related to OS and DSS were used to establish the nomogram, which was assessed via the concordance index (C-index), and calibration curve. An internal validation was conducted to test the accuracy and effectiveness of the nomogram. Kaplan–Meier calculation was used to predict the further OS and DSS status of these patients. Results: On multivariate Cox proportional hazards regression, the independent prognostic risk factors associated with OS were age, surgery, chemotherapy, regional node positive (RNP), extension range and distant metastasis with a moderate C-index of 0.731 (95% confidence interval (CI): 0.719-0.744) and 0.766 (95% CI: 0.747-0.785) in the development and verification groups, respectively. While, marital status, surgery, chemotherapy, regional node positive (RNP), extension range and distant metastasis were significantly linked to AC patients’ DSS, which have a better C-index of 0.756 (95% confidence interval (CI): 0.741-0.770) and 0.781 (95% CI: 0.757-0.805) in the development and verification groups. Both the survival calibration curves of 3- and 5-year OS and DSS brought out a high consistency. Conclusion: Our study yielded a satisfactory nomogram showing the survival of AC patients, which may help clinicians to assess the situation of AC patients and implement further treatment.